(3eTLQ GdQLGd GdKbGJ GdPjf GMGOjKge UMjMIs - (3GdYGedj GdCaJhfj GdZQhj, CHh UGdM, GdegOj, eMeO Hf HgGA GdOjf eMeO, J (B1183 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3hefg jYde GdWHbGJ hcd MOjK UMjM aj CMO GdCUhd GdCQHYI eeG JYdb HGdCMcGe aEf SfOg ehLhO gfG Ydi eG gh Ydjg aj Jdc GdcJH hKO UQaJ aj GJeGe gPG GdeTLQ CjGeG eJhGdjI hdjGdj eJYGbHI (B...s
(3BNQgG (B:s
(3YHO Gddg Hf jMji Gd(B.... (3Qhi heMeO Hf YeQ Hf SYjO V Qhi Nda Hf LGOQhjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B2\1541s
(3GdPQjYI (B2\1541s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs